Mellan strategi och vardag - Bergön,Elin; Haraldsson,Alicia (2026)
The labour market has become increasingly dynamic, characterised by technological change, greater job mobility and shifting employee expectations. As employees place growing importance on development, work environment and work-life balance, organisations face new challenges in retaining talent. One strategy to retain employees is internal employer branding. As engineers have good opportunities to change employers, it is therefore relevant to examine how an organisation with a large engineering workforce works with internal employer branding. The purpose of this study is to explore how the employer branding strategists within the company work with internal employer branding and how it is perceived by its employees, particularly engineers as a professional group. The study adopts a qualitative research approach and is based on semi-structured interviews with employer branding strategists and engineers working in a large organization within the technology sector. The empirical material was analyzed using thematic analysis. The findings show that internal employer branding is primarily expressed through organizational culture, activities, internal communication, and opportunities for learning and development. While learning and development appear to be a well established and shared priority within the organization, discrepancies emerge between organizational intentions and employee experiences regarding activities and communication. These differences highlight gaps between expressed intentions and actual everyday practices. The study contributes to a deeper understanding of internal employer branding in this engineering organization and emphasizes the importance of aligning organizational initiatives with employees’ experiences.
Keywords: Internal employer branding; organizational culture; engineers; learning and development; internal communication; psychological safety; employee experience